Assessment of ductile iron casting process with the use of the DRSA method - Kujawińska A.; Rogalewicz M.; Diering M.; Piłacińska M.; Hamrol A.; Kochańskib A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The paper introduces a concept of assessment of a ductile iron casting process with use of the rule-based approach, known as DRSA (dominance-based rough set approach). The research was conducted in a large Polish foundry. The collected data concern the chemical composition and mechanical properties of the used ductile cast iron. In the paper, a methodology of creating a rule-based moulding model for the tensile strength was proposed. The quality, sensitivity and accuracy of the model extracted from the data were examined. The studies proved its usefulness in the industrial practice and for aiding of the decision making process.